PENGARUH STRATEGI EVERYONE IS A TEACHER HERE TERHADAP KETERAMPILAN BERKOMUNIKASI DAN HASIL BELAJAR IPA SISWA KELAS V SEKOLAH DASAR - Nahdiyyah, Dea; Ririn Andriani Kumala Dewi; , Kiki Fatkhiyani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This research aims to determine the effect of the Everyone is a teacher here strategy on communication skills and student learning outcomes, as well as determine the increase in student learning outcomes using the Everyone is a teacher here strategy. This research uses a quantitative method with a True Experimental research design in the form of Pretest-Posttest Control Group Design. This research data was collected through written tests and observation sheets. Statistical results using the independent sample t test, for communication skills, a significance value of 0.041 with α = 0.05 was obtained. So, it can be stated that there is an influence. Statistical results on learning outcomes using the independent sample t test, obtained a significance value of 0.000 with α = 0.05. Thus, it can be concluded that there is an influence of the Everyone is a teacher here strategy on communication skills and student learning outcomes. The statistical results using the N-Gain test in the experimental class were 0.51, which is included in the moderate interpretation. Meanwhile, the N-Gain value in the control class is 0.29, which is included in the low interpretation. Thus, it can be concluded that there is an increase in learning outcomes after being given treatment using the Everyone is a Teacher Here Strategy.